Originally Posted by **ferdo**

Ok, the question we got was to identify and explain one critical error in the factoring example.

this is the example:

X=X

X Exponent 2 = X Exponent 2

X Exponent 2 - X Exponent 2 = X Exponent 2 - X Exponent 2

X(X - X) = (X + X) (X - X)

X(X - X) = (X + X) (X - X)

-------- --------------

(X - X) (X - X)

X = (X + X)

X = 2X

If we let X = 1, then upon substitution we have

(1) = 2(1)

1 = 2

I think the problem lies in line 3 right side, (X + X) (X - X), should it be like the left side X(X - X)?

Thanks for your help.